Social Role of Alms (zakāt) in Islamic Economies - Bukowski, Adam (Annales. Etyka w Życiu Gospodarczym, 2014)
Islam as both religion and socioeconomic system is based on five main pillars, that is – five basic acts considered mandatory by Muslims, summarized in the hadith of Gabriel. One of them is zakāt (almsgiving), i.e. giving 2.5% of one’s wealth to the poor and needy. In contrary to Christian religion, where question of charity is rather of a voluntary matter, the role of zakāt in Islam is much more rigidly described. Almsgiving is considered as a duty of a pious Muslim towards the poor. Thus in Islamic economy, strongly based on Islam principles given by Allah to Muhammad, zakāt is imposed by law and is not considered a charity but duty rather. The notion of zakāt is mentioned in Qur-an over a 100 times, solely or in conjunction with other commandments. On a basis that zakāt is to be paid as a part of total wealth exceeding given minimum wealth (nisab) it is then justifiable to say that zakāt is principally a tax. A role of this essay is to shed some light on a utilisation and role of zakāt in Islamic economies in socioeconomic context, with an example of Islamic Republic of Pakistan, where in 1980 the Zakāt Ordinance was imposed. The concept of zakāt is present in many Islamic countries, but its nature varies, being dependent from the interpretation of religious law in a given country. Everywhere though, its social role as an important tool maintaining social justice is strongly expressed. Of course zakāt system also has its drawbacks and is subjected to much criticism. The article aims to present both advantages and negative aspects of zakāt.